Exercise to Improve Sleep in Insomnia: Exploration of the Bidirectional Effects - Baron, Kelly Glazer; Reid, Kathryn J.; Zee, Phyllis C. (Journal of clinical sleep medicine, 2013)
Exercise improves sleep quality, mood, and quality of life among older adults with insomnia. The purpose of the study was to evaluate the daily bidirectional relationships between exercise and sleep in a sample of women with insomnia. Participants included 11 women (age M = 61.27, SD 4.15) with insomnia who engaged in 30 min of aerobic exercise 3 times per week. Self-reported sleep quality was assessed at baseline and at 16 weeks. Sleep and exercise logs and wrist activity were collected continuously. Sleep variables included subjective sleep quality and objective measures recorded via wrist actigraphy (sleep onset latency [SOL], total sleep time [TST], sleep efficiency [SE], wake after sleep onset [WASO], and fragmentation index [FI]). Age, subjective sleep quality, TST, SOL, and physical fitness at baseline were tested as moderators of the daily effects. TST, SE, and self-reported global sleep quality improved from baseline to 16 weeks (p values < 0.05). Baseline ratings of sleepiness were negatively correlated with exercise session duration (p < 0.05). Daily exercise was not associated with subjective or objective sleep variables during the corresponding night. However, participants had shorter exercise duration following nights with longer SOL (p < 0.05). TST at baseline moderated the daily relationship between TST and next day exercise duration (p < 0.05). The relationship between shorter TST and shorter next day exercise was stronger in participants who had shorter TST at baseline. Results suggest that sleep influences next day exercise rather than exercise influencing sleep. The relationship between TST and next day exercise was stronger for those with shorter TST at baseline. These results suggest that improving sleep may encourage exercise participation.